DAKWAH MILENIAL ERA DIGITAL: ANALISIS LINGUISTIK KOGNITIF PADA LAGU BALASAN JARAN GOYANG - Dwi Kurniasih (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
This study aims to deliver the message of representation for the milenial generation in the digital era. The method used in this research is descriptive qualitative, which describe the objects based on reality. Data from this research are the lyrics of Jaran Goyang song and The Reply Song of Jaran Goyang. The technique used to analyze data is qualitative content analysis. Results of this study indicate that the milenial generation utilizes Youtube social media accounts to carry out da'wa activities by changing the song Jaran Goyang which is titled The Reply Song of Jaran Goyang intos lyrics filled with da’wa messages. Results of this study indicate that the da'wa language in the songs analyzed uses cognitive-linguistic aspects in a cognitive semantic perspective that contains the meaning of da'wa, namely the invitation to perform night prayers, recites the Al-Qur’an, and avoid shirk.